Latent profiles of impulsivity facets and associations with drinking behaviors. (1st November 2021) - Stamates, A.L.; Schulz, C.T.; Ehlke, S.J.; Thompson, L.; Lau-Barraco, C.; Kelley, M.L.
Highlights: Latent profile analysis examined typologies across UPPS-P facets. A 3-profile solution was found with Low, Moderate, and Highest levels of UPPS-P facets. Profiles did not vary on drinking behaviors but differed on alcohol-related problems. Moderate and Highest UPPS-P groups reported greater drinking to cope motivations. The Highest UPPS-P group reported greater drinking to conform motivations. Abstract: Background: Impulsivity is positively associated with alcohol use. However, scant research has used person-centered approaches to examine how patterns of impulsivity facets may be associated with alcohol-related outcomes. Consequently, the present study sought to (1) identify latent groups of individuals who share similarities based on the five facets of impulsivity assessed using the UPPS-P scale (positive urgency, negative urgency, premeditation, perseverance, and sensation seeking) and (2) examine differences between latent profiles on alcohol use (i.e., typical alcohol quantity, typical alcohol frequency, binge frequency), alcohol consequences, and drinking motivations. Methods: Participants were 360 ( M age = 21.83; 78.9 % female; 49.4 % racial/ethnic minority) college students who reported weekly drinking over the prior 30 days. They completed questionnaires of impulsivity, alcohol use behaviors, alcohol consequences, and drinking motivations. Latent profile analysis was used to identify classes based on the five UPPS-P facets as indicators. Results: Results revealed that three classes best fit the data: Highest UPPS-P (14.4 %); Moderate UPPS-P (56.9 %); and Lowest UPPS-P (28.6 %). Profiles did not vary on drinking behaviors (quantity, frequency, or binge frequency), but significant differences were observed on alcohol consequences and drinking motivations, specifically coping and conformity motives. Conclusions: Our data demonstrated that UPPS-P facets tend to cluster together, and patterns may pose risk for consequences and negative motives for drinking. The current study contributed to the conceptualization of impulsivity by identifying specific impulsivity typologies that may be used to target individuals at elevated risk for alcohol consequences.